Modern information technologies of creating documents according to quality management standards based on ISO 9000 - Yarka, Ulyana; Myna, Zhanna; Peleschyshyn, Oksana; Bilushchak, Тetiana (НТУ "ХПІ", 2016)
Introduction of quality management system (QMS) according to the international standard ISO 9001-2008 enhances the providing of European quality service, which is issue number one for Ukraine. The process of standardization involves huge amount of paperwork and thus arises the question of rational approach to creation methods of such documentation in view of its peculiarities. The software and various methodologies for the creation of such documents have been considered. The main focus has been on the free software, to which there is unlimited access in the Internet. One of the universal methods of work automation is creating document templates. The information technologies of creating such templates based documents with the help of OpenOffice.org and with additional use of built in programming language of OpenOffice.org. Basic are presented. The introduction of such templates will enable complying with the requirements of standardization, avoiding mistakes, ensuring the minimum time of QMS processing of documents, and thus improving the quality of work and introduc ing the given standards.

У статті розглядається впровадження системи управління якістю СУЯ відповідно до міжнародного стандарту ISO 9001-2008. Відповідність вимогам стандарту ISO 9001 свідчить про певний рівень надійності постачальника, послуги і стабільність його організації. Щоб впровадити ці стандарти, необхідно правильно і ефективно налагодити роботу щодо створенню їх документації. Для спрощення роботи з документами пропонується засоби автоматизації процесу створення шаблонів. Представлені інформаційні технології створення таких шаблонів на основі можливостей пакету OpenOffice.org і з додатковим використанням вбудованої мови програмування OpenOffice.org. Basic.
Сучасні інформаційні технології створення документації згідно стандартів управління якістю на основі ISO 9000
Keywords: quality management system; standards; ISO 9001; modern information technologies; document templates; система контролю якості; стандарти; ISO 9001; шаблони документів